The Third Generation Anti-HER2 Chimeric Antigen Receptor Mouse T Cells Alone or Together With Anti-PD1 Antibody Inhibits the Growth of Mouse Breast Tumor Cells Expressing HER2 in vitro and in Immune Competent Mice - Li, Panyuan; Yang, Lingcong; Li, Tong; Bin, Shufang; Sun, Bohao; Huang, Yuting; Yang, Kaiyan; Shan, Daming; Gu, Haihua; Li, Hongzhi (Frontiers in Oncology, 2020)
Chimeric Antigen Receptor (CAR)-T cell therapy is very effective against CD19+ leukemia but its efficacy for solid tumors is still limited. This study explored the efficacy of third generation anti-HER2 CAR-T cells alone or in combination with PD1 blockade on HER2+ breast tumor cells in vitro and in immune competent mouse model. The PDL1-positive mouse breast tumor cell line 4T1 engineered to express luciferase and human HER2 was used as the target cell line (4T1-Luc-HER2). Anti-HER2 CAR-T cells were generated by transducing mouse spleen T cells with recombinant lentiviruses. ELISA analysis showed that IL-2 and IFN-γ secretion from CAR-T cells co-cultured with target cells was increased, and this secretion was increased further with the addition of anti-PD1 antibody. Lactate dehydrogenase assay revealed that CAR-T cells displayed a potent cytotoxicity against target cells, and the addition of anti-PD1 antibody enhanced the cytotoxicity. At the effector: target ratio of 16:1, cytotoxicity was 39.8% with CAR-T cells alone, and increased to 49.5% with the addition of anti-PD1 antibody. In immune competent syngeneic mouse model, CAR-T cells were found to infiltrate into tumors, inhibit tumor growth and increase tumor apoptosis significantly. Addition of anti-PD1 antibody could enhance these anti-tumor activities. Twenty-one days after treatment, compared with blank T group, tumor weight was reduced by 50.0% and 73.3% in CAR-T group and CAR-T plus anti-PD1 group. Our results indicate that anti-PD1 antibody can greatly improve the efficacy of anti-HER2 CAR-T against HER2-positive solid tumors.